Detection of Helminth Eggs and Identification of Hookworm Species in Stray Cats, Dogs and Soil from Klang Valley, Malaysia - Tun, S.; Ithoi, I.; Mahmud, R.; Samsudin, N.I.; Heng, C.K.; Ling, L.Y. (Public Library of Science, 2015)
The present study was conducted to determine the prevalence of helminth eggs excreted in the faeces of stray cats, dogs and in soil samples. A total of 505 fresh samples of faeces (from 227 dogs and 152 cats) and soil were collected. The egg stage was detected via microscopy after the application of formalin-ether concentration technique. Genomic DNA was extracted from the samples containing hookworm eggs and used for further identification to the species level using real-time polymerase chain reaction coupled with high resolution melting analysis. Microscopic observation showed that the overall prevalence of helminth eggs among stray cats and dogs was 75.7% (95% CI = 71.2%-79.9%), in which 87.7% of dogs and 57.9% of cats were infected with at least one parasite genus. Five genera of heliminth eggs were detected in the faecal samples, including hookworms (46.4%), Toxocara (11.1%), Trichuris (8.4%), Spirometra (7.4%) and Ascaris (2.4%). The prevalence of helminth infections among stray dogs was significantly higher than that among stray cats (p < 0.001). Only three genera of helminths were detected in soil samples with the prevalence of 23% (95% CI = 15.1%-31%), consisting of hookworms (16.6%), Ascaris (4%) and Toxocara (2.4%). The molecular identification of hookworm species revealed that Ancylostoma ceylanicum was dominant in both faecal and soil samples. The dog hookworm, Ancylostoma caninum, was also detected among cats, which is the first such occurrence reported in Malaysia till date. This finding indicated that there was a cross-infection of A. caninum between stray cats and dogs because of their coexistent within human communities. Taken together, these data suggest the potential role of stray cats and dogs as being the main sources of environmental contamination as well as for human infections.